Method for chemically modifying fullerene C60 carrier and its application in electrochemical hydrogenation of soybean oil
The preparation of high-active C60/Pt catalysts by chemically modifying fullerene C60 has solved the problems of high trans fatty acid content and poor catalyst stability in the traditional hydrogenation process, achieved efficient hydrogenation under mild conditions, and provided low-TFAs hydrogenated oil Industrial production foundation.
Patent Information
- Application Number
- CN202211635451.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The hydrogenated oil produced by traditional hydrogenation processes under high temperature and high pressure conditions has a high content of trans fatty acids, which affects health. The mechanical strength and load capacity of commonly used carbon-loaded platinum catalysts are limited, resulting in poor hydrogenation efficiency and stability.
采用化学修饰富勒烯C60作为载体,通过超声波处理和分散剂的加入,制备出高活性和稳定的C60/Pt催化剂,用于SPE电化学氢化反应中,降低反式脂肪酸生成并提高催化剂的机械强度和负载能力。
Hydrogenation under mild conditions is achieved, which significantly reduces the generation of trans fatty acids, improves the stability and hydrogenation efficiency of the catalyst, and provides data accumulation and technical basis for large-scale industrial production.
Smart Images

Figure CN116005184B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Pt-based catalyst, in particular to a fullerene C60 / Pt catalyst and application thereof in electrochemical hydrogenation of soybean oil. Background Art
[0002] After hydrogenation, the melting point and plasticity of vegetable oils are improved, and they are used as raw materials for many products in the food industry. However, the traditional hydrogenation process is often carried out under high temperature and high pressure conditions, and the hydrogenated oil produced by this hydrogenation process has a high content of trans fatty acids (TFAs). Current studies have shown that the intake of TFAs is closely related to the induction of Alzheimer's disease, cardiovascular disease, diabetes and liver damage. The solid polymer electrolyte (SPE) electrochemical hydrogenation reaction device is a new type of hydrogenation process that induces addition reactions of double bonds in oils and fats through an external electric field. It has the advantages of mild production conditions, controllable preparation process, no need for high temperature and high pressure, and low TFAs content in the product.
[0003] The core component of the SPE reactor is the membrane electrode assembly (MEA) composed of a proton exchange membrane and carbon paper sprayed with a catalyst. It is the main place for the hydrogenation reaction. The catalyst used in the MEA is closely related to the hydrogenation effect of the reactor. At present, the most commonly used commercial carbon-supported platinum (Pt / C) catalyst in oil hydrogenation is a Pt-based catalyst, using amorphous carbon black as a catalyst carrier. However, due to the irregular structure of amorphous carbon, limited mechanical strength and loading capacity, the amount of catalyst loaded on it as a carrier is limited, and as the reaction proceeds, the amorphous carbon is gradually destroyed, and the Pt loaded on it also falls off and agglomerates, resulting in poor hydrogenation efficiency and catalytic stability. Summary of the invention
[0004] The purpose of the present invention is to provide a method for chemically modifying a fullerene C60 carrier and its application in electrochemical hydrogenation of soybean oil. The research is carried out from the perspective of introducing a dispersant, and a fullerene C60 catalyst carrier with high catalytic activity and good stability is obtained, which gives full play to the characteristics of the SPE reactor, provides ideas for the improvement of the new hydrogenation process, and provides the possibility for large-scale preparation of low TFAs hydrogenated oil. In the food field where hydrogenated oils are widely used, the present invention provides data accumulation for large-scale industrial production of SPE hydrogenation technology and lays a foundation.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for chemically modifying a fullerene C60 carrier comprises the following steps:
[0007] Weigh 5-15 mg of C60 / Pt catalyst, place it in a centrifuge tube, add 5-15 mg of isopropanol; add a dispersant, ultrasonicate for 5-15 min, add a binder, and continue ultrasonicating for 40-60 min. After the ultrasonication, let it stand for 12-48 h to obtain a chemically modified fullerene C60 / Pt catalyst, wherein:
[0008] The preparation method of the C60 / Pt catalyst is as follows:
[0009] (1) Purification and oxidation of fullerenes
[0010] Take 4-6g of fullerene sample with a particle size of 20-400nm and mix it with 2.0-3.0g NaNO 3 After uniform mixing, add 100-150 mL of concentrated H 2 SO 4 , stir in an ice bath for 60-120 min, then slowly add 10-20 g KMnO 4 , remove the ice bath and stir for 30 to 60 minutes; after the reaction is complete, slowly add the obtained slurry into 200 to 250 mL of ultrapure water, control the temperature to 80 to 100 ° C, stir evenly for 0.5 to 1.5 hours, and then add 3% H 2 O 2 The solution and warm water were adjusted to 700 mL; 30% (v / v) HCl was used for multiple washings, and a slurry was obtained after filtration, which was placed in a vacuum drying oven at 60-80° C. and dried for 1-3 h to obtain oxidized C60;
[0011] (2) Preparation of C60 / Pt catalyst by liquid phase reduction method
[0012] Take 50-55 mg of oxidized C60 and add it to 200-250 mL of ultrapure water, and ultrasonicate it for 30-90 min to obtain a catalyst carrier suspension; then add 5-15 mL of 0.01-0.05 mol / L H 2 PtCl 6 solution, and adjust the pH to 11-12 with 0.5-1.5 mol / L NaOH; measure 1-3 g NaBH 4 Add to the liquid phase and stir at room temperature for 25 to 30 hours. After the reaction is completed, wash with ultrapure water until the pH value is neutral, filter and dry the obtained slurry in a vacuum drying oven at 60 to 80°C for 1 to 3 hours to obtain a fullerene C60 loaded with Pt catalyst, wherein the Pt content in the C60 / Pt catalyst is 10 to 90%;
[0013] The amount of the dispersant added is 0.05-1% of the mass of the C60 / Pt catalyst, and the amount of the binder added is 5-40% of the mass of the C60 / Pt catalyst;
[0014] The dispersant is Tween (Tween 20, Tween 40, Tween 60, Tween 80) or polyethylene glycol (molecular weight of 1000-8000;
[0015] The adhesive is a mixture of polytetrafluoroethylene emulsion and Nafion solution, the mass ratio of polytetrafluoroethylene to Nafion solution is 1:1, the mass concentration of polytetrafluoroethylene emulsion is 5-40%, and the mass concentration of Nafion solution is 5-40%.
[0016] The chemically modified fullerene C60 / Pt catalyst prepared by the above method can be used as a cathode catalyst in an SPE electrochemical hydrogenation reactor.
[0017] The chemically modified fullerene C60 / Pt catalyst prepared by the above method can be used as a hydrogenation reaction catalyst.
[0018] The chemically modified fullerene C60 / Pt catalyst prepared by the above method can be used as an SPE cathode catalyst in the electrochemical hydrogenation of soybean oil. The reaction conditions are: reaction temperature 30-80°C, oil phase flow rate 20-90 mL / min, water phase flow rate 20-90 mL / min, cathode catalyst loading 0.1-0.8 mg / cm 2 , the anode catalyst is RuO 2 , the anode catalyst loading is 0.1~0.8mg / cm 2 .
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] The present invention utilizes an SPE hydrogenation reactor to hydrogenate soybean oil, and optimizes the oil hydrogenation process from the perspective of chemically modifying the fullerene C60 carrier. As a nanomaterial, fullerene C60 has the characteristics of high mechanical strength, large specific surface area, and good electrical conductivity. It is an excellent material as a carrier. The spherical structure can provide more attachment sites. At the same time, the special structure can maintain a better morphology in a complex environment, ensuring the integrity of the nanostructure. Due to the modification of the chemical method to introduce a dispersant to modify the fullerene C60, the adverse effects of the aggregation of the fullerene C60 itself and the shedding of Pt particles during the hydrogenation process on the hydrogenation reaction can be effectively avoided. As a carbon-based material, fullerene C60 has good electrical conductivity, can provide a higher current density for the catalyst, give full play to the catalytic performance of the Pt particles, and improve the efficiency of oil hydrogenation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1For the sedimentation experiment of adding different concentrations of catalyst system, No. 1 is C60 / Pt blank control, 2 is added with 0.05% Tween-80; 3 is added with 0.25% Tween-80; 4 is added with 1.00% Tween-80; 5 is added with 0.05% polyethylene glycol-6000; 6 is added with 0.25% polyethylene glycol-6000; 7 is added with 1% polyethylene glycol-6000;
[0022] Figure 2 is the sedimentation stability of dispersant systems with different mass fractions;
[0023] Figure 3 Particle size distribution of C60 / Pt with Tween-80 added;
[0024] Figure 4 Particle size distribution of C60 / Pt with polyethylene glycol-6000 added;
[0025] Figure 5 The potential of C60 / Pt with the addition of Tween-80 and polyethylene glycol-6000. In the figure, the letters in the data columns marked with letters are inconsistent, indicating significant differences (p<0.05), and the same letters indicate no significant differences (p<0.05). Capital letters indicate significant differences between the addition amounts of polyethylene glycol-6000, and lowercase letters indicate significant differences between the addition amounts of Tween-80.
[0026] Figure 6 Transmission electron micrographs of C60 / Pt with and without dispersant, A is C60 / Pt without dispersant; B and C are C60 / Pt with 0.25% Tween-80; D and E are C60 / Pt with 0.05% polyethylene glycol-6000 (B and D are magnified 10,000 times; C and E are magnified 30,000 times);
[0027] Figure 7 is the XRD spectrum of the catalyst after adding Tween-80;
[0028] Figure 8 is the standard curve of platinum standard solution and absorbance;
[0029] Fig. 9 C60 / Pt + and C60 / Pt catalytic activity;
[0030] Fig.10 The effect of different catalyst dosages on the iodine value of hydrogenated oil;
[0031] Fig.11 The effect of different catalyst dosages on hydrogenation resistance;
[0032] Fig.12 The effect of different hydrogenation temperatures on the iodine value of hydrogenated oil;
[0033] Fig.13 The effect of different hydrogenation temperatures on hydrogenation resistance;
[0034] Fig.14 The effect of different oil phase flow rates on the iodine value of hydrogenated oil;
[0035] Fig.15 The effect of different oil phase flow rates on hydrogenation resistance;
[0036] Fig.16 The effect of different hydrogenation times on the iodine value of hydrogenated oil;
[0037] Fig.17 Soybean oil (left) and C60 / Pt+ hydrogenated oil (right);
[0038] Fig.18 Analysis of aroma and flavor components of soybean oil (A), C60 / Pt (B) and C60 / Pt+ (C) hydrogenated oil;
[0039] Fig.19 PCA analysis diagram of soybean oil, C60 / Pt and C60 / Pt+hydrogenated oil;
[0040] Fig. 20 Melting (left) and crystallization (right) curves of soybean oil (A), C60 / Pt (B) and C60 / Pt+ (C) hydrogenated oil;
[0041] Fig.21 Crystallization of hydrogenated oils of soybean oil (A), C60 / Pt (B) and C60 / Pt+ (C). DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0043] The present invention provides a method for chemically modifying a fullerene C60 carrier, the method comprising the following steps:
[0044] Step 1: Purification and oxidation of fullerenes
[0045] Take 5g of fullerene sample with a particle size of 100nm and mix it with 2.5g of NaNO 3 After mixing evenly, add 120 mL of concentrated H 2 SO 4 , stir in ice bath for 60 min, then slowly add 15 g KMnO 4, remove the ice bath and stir for 30 min; after the reaction is complete, slowly add the obtained slurry into 230 mL of ultrapure water, control the temperature to 90 ° C, stir evenly for 1 h, and then add 3% H 2 O 2 The solution was diluted with warm water to 700 mL; the solution was washed several times with 30% (v / v) HCl, and a slurry was obtained after filtration, which was placed in a vacuum drying oven at 60° C. and dried for 2 h to obtain oxidized C60.
[0046] Step 2: Preparation of catalyst by liquid phase reduction method
[0047] 51 mg of oxidized C60 was added to 240 mL of ultrapure water and ultrasonically treated for 60 min to obtain a catalyst support suspension; then 10 mL of 0.02 mol / L H 2 PtCl 6 Solution, and adjust pH to 11.86 with 1mol / LNaOH. Accurately weigh 2gNaBH 4 , slowly add to the liquid phase several times, and stir at room temperature for 26 hours. After the reaction is completed, wash with ultrapure water several times until the pH value is neutral. Filter and dry the obtained slurry in a vacuum drying oven at 60°C for 2 hours to obtain a catalyst of fullerene C60 loaded with Pt, namely: C60 / Pt catalyst.
[0048] Step 3: Chemical modification of C60 / Pt catalyst
[0049] Weigh 10 mg of C60 / Pt catalyst, place it in a 4 ml PE centrifuge tube, add 10 mg of isopropanol; add 0.05%, 0.25% and 1% of Tween-80 and 0.05%, 0.25% and 1% of polyethylene glycol 6000 respectively, after ultrasonic treatment for 10 minutes, add 30% of binder (polytetrafluoroethylene emulsion (solid content 5%) and Nafion solution (5%) 15% each), and continue ultrasonic treatment for 50 minutes. After the end of ultrasonic treatment, stand for 12 hours, 24 hours, 36 hours and 48 hours respectively to obtain chemically modified fullerene C60 / Pt catalyst.
[0050] Results and Analysis:
[0051] 1. Comparative analysis of C60 / Pt with and without dispersant
[0052] Tween-80 and polyethylene glycol-6000 surfactants were used to disperse C60 / Pt. Agglomerates were opened by grinding, magnetic stirring and ultrasonic treatment, and dispersed under the action of surfactants. Sedimentation test, laser particle size distribution and TEM were used to characterize the dispersion stability, particle size distribution and morphology of the dispersant, so as to select the dispersant with the best dispersion effect and its optimal addition amount. Finally, XRD and determination of the platinum content of the catalyst were used to determine the specific amount of the catalyst used in the electrohydrogenation experiment.
[0053] 1. Sedimentation test
[0054] In the same mass of C60 / Pt-isopropanol system, two dispersants, polyethylene glycol-6000 and Tween-80, were added with mass fractions of 0.05%, 0.25% and 1.00%, respectively; the sedimentation effect after standing for 48 hours after ultrasound is shown in Figure 1. Figure 2 The figure is a relationship curve between the volume V of the upper liquid and the amount of dispersant added. The present invention uses the volume V of the upper liquid to measure the dispersing effect of dispersants with different contents on the catalyst, that is, the larger the volume V, the less precipitation in the system, and the better the dispersing effect on the catalyst.
[0055] from Figure 1 It can be seen that after adding the dispersant, the dispersion effect of the catalyst is improved. This is because the dispersant type selected in the present invention is a non-ionic surfactant, whose hydrophilic group is adsorbed on the catalyst surface by van der Waals force, changing the surface state of the catalyst, thereby improving its dispersibility.
[0056] from Figure 2 It can be seen that the amount of dispersant added has a significant difference in the dispersing effect of the catalyst (p≤0.05). When Tween-80 is selected as the dispersant, as the amount of Tween-80 added increases, the dispersion effect of the catalyst shows a trend of first rising and then falling, and when the amount of Tween-80 added is 0.25%, the dispersion effect of the system is the best. Too much or too little dispersant will lead to poor catalyst dispersion. This may be because when the dispersant concentration exceeds the optimal value, the adsorption is oversaturated, resulting in a decrease in the hydrophilicity of the catalyst surface, which is not conducive to dispersion; and when the dispersant concentration is low, it cannot fully wet the emulsified catalyst surface, making the dispersion effect worse. When polyethylene glycol-6000 is selected as the dispersant, as its addition amount increases, the dispersion effect of the catalyst shows a trend of gradually decreasing, and the optimal addition amount is 0.05%. In addition, different dispersants have different dispersing effects on catalysts. When the addition amounts of the two dispersants are optimal, the sedimentation stability of polyethylene glycol-6000 is 0.05 lower than that of Tween-80. This may be because polyethylene glycol-6000 has a straight-chain structure and is adsorbed on the surface of the catalyst in the form of point contact, resulting in an unstable system and a dispersion effect inferior to that of Tween-80.
[0057] 2. Particle size and potential analysis
[0058] In order to further explore the effect of adding dispersant on the particle size and potential of catalyst C60 / Pt, the particle size and potential before and after adding dispersant were characterized by laser particle size analyzer and potential analyzer.
[0059] Figure 3 The particle size distribution of C60 / Pt after adding different mass fractions of Tween-80. It can be seen from the figure that when no dispersant is added, the particle size distribution curve of C60 / Pt has a peak; the particle size distribution of the catalyst particles is wide, with an average particle size of about 200nm and a particle size volume distribution of about 27%; in addition, a part of the particle size distribution is between 200 and 350nm, which indicates that the catalyst itself has agglomeration. When Tween-80 is added, this phenomenon changes, and the role of dispersants of different mass fractions is also different; when 0.25% Tween-80 is added, the particle size distribution of the catalyst particles becomes narrower than that without adding dispersant, with an average particle size of about 155nm and an overall particle size distribution of about 28%, which indicates that adding 0.25% Tween-80 can significantly improve the particle size of C60 / Pt and increase its volume distribution at the peak, effectively improving the dispersion effect. After adding 0.05% and 1% Tween-80, the particle size distribution curves of C60 / Pt treated by the two methods are similar, with the average particle size of about 210nm, and the obtained C60 / Pt particle size distribution becomes wider. Although the addition of these two mass fractions leads to an increase in the average particle size, the particle size volume distribution is greater than 30%, which also shows that adding too much or too little dispersant is not conducive to the dispersion of the catalyst.
[0060] from Figure 4It can be seen that the change in the average particle size of C60 / Pt is positively correlated with the addition amount of polyethylene glycol-6000. When the addition amount of polyethylene glycol-6000 is 0.05%, the particle size distribution of C60 / Pt is between 100 and 250 nm, which is better than the particle size distribution of C60 / Pt without adding dispersant. At this time, the average particle size of C60 / Pt is the smallest, which is 152 nm. With the increase of the addition amount of polyethylene glycol-6000, the average particle size of C60 / Pt also gradually increases. This may be because polyethylene glycol 6000 contains two hydrophilic groups, namely hydroxyl groups. and ether bonds, and does not contain hydrophobic groups, which makes it have good water solubility and acid-base stability; in addition, polyethylene glycol-6000 is serpentine in aqueous solution, and is easy to form strong hydrogen bonds with the surface of catalyst particles, and its ether bonds are also easy to form affinity with the catalyst surface, so polyethylene glycol-6000 is easy to adsorb on the surface of particles, thereby forming a layer of polymer film to wrap the catalyst particles; a protective film with a certain thickness is formed on the surface of catalyst particles, showing a steric hindrance effect, greatly weakening the attraction between particles, thereby effectively preventing the growth of particles and inhibiting the agglomeration of particles. When the addition amount is 1%, the particle size distribution of C60 / Pt is wider, between 200 and 500nm, and the average particle size is significantly increased to about 300nm, which indicates that too much polyethylene glycol-6000 can aggravate the agglomeration of C60 / Pt and cannot better play its steric hindrance effect.
[0061] like Figure 5 As shown in the figure, the Zeta potential of C60 / Pt decreases first and then increases with the increase of Tween-80 addition, while after adding polyethylene glycol-6000 dispersant, the Zeta potential of C60 / Pt shows the opposite trend, and the Zeta potential gradually increases with the increase of addition. The change trend of Zeta potential is the same as that of its average particle size, which means that the larger the particle size, the larger the Zeta potential value, and the more stable the suspension system. When the addition amount of polyethylene glycol-6000 is 1%, its potential is -29.3mV, because the increase of polyethylene glycol-6000 addition is conducive to the improvement of the Zeta potential value of the particle surface. Therefore, the Zeta potential value of the catalyst surface in the 1% polyethylene glycol-6000 suspension is higher.
[0062] 3. Transmission electron microscopy analysis
[0063] According to the sedimentation experiment and the particle size and potential analysis, the addition of 0.25% Tween-80 and 0.05% polyethylene glycol-6000 has a good dispersion effect on C60 / Pt, and its sedimentation stability and average particle size are better than those of C60 / Pt without dispersant. Transmission electron microscopy was used to characterize C60 / Pt with 0.25% Tween-80 and 0.05% polyethylene glycol-6000. Figure 6TEM images of C60 / Pt (a), C60 / Pt with 0.25% Tween-80 added (b), and C60 / Pt with 0.05% polyethylene glycol-6000 added (c).
[0064] from Figure 6 In A, the basic conformation of C60 / Pt can be clearly seen. Pt (black dots in the gray shadow) has been loaded on C60 (gray shadow); C60 particles are agglomerated together, which is caused by the fact that the surface of nano-scale particles is very prone to agglomeration; and combined with the electron microscope ruler, it can be calculated that the diameter of C60 particles is about 180nm. In addition, Pt has a larger crystal particle size, which can reach 50nm.
[0065] After adding 0.25% Tween-80, the surface of C60 molecules is obviously wrapped by the dispersant as shown in Figure B. In addition, due to the addition of Tween-80, it can be seen that the amount of Pt on the surface of C60 has increased and appears spherical. This is because the addition of the dispersant gives C60 a larger specific surface area and more binding sites. The molecular structure of C60 itself is football-shaped, so the Pt loaded on C60 also appears football-shaped, as shown in Figure B. Figure 6 As shown in C, combined with the electron microscope ruler, it can be calculated that the diameter of C60 / Pt is about 10nm.
[0066] When polyethylene glycol-6000 is introduced into the C60 / Pt system, C60 is also wrapped by polyethylene glycol-6000, such as Figure 6 As shown in D and E, Pt is loaded on the surface of C60 in the shape of a football. Combined with the electron microscope ruler, it can be calculated that the diameter of C60 / Pt is about 15nm. In addition, the carbon-carbon bond in the C60 molecule is a special bond between a single bond and a double bond. The bond between the benzene ring and the benzene ring is called a [6,6] bond. This bond has more olefin properties and is an active site for chemical reactions. It has a strong ability to react with free radicals and is conducive to combining with Pt. Polyethylene glycol-6000 and Tween-80 are both non-ionic surfactants. After being wrapped on the surface of C60, they can produce a steric hindrance effect between each other, resulting in a reduced probability of collision between catalyst particles, achieving a better dispersion effect.
[0067] 3. X-ray diffraction analysis
[0068] According to the results of sedimentation experiment, transmission electron microscope, particle size and potential analysis, 0.25% Tween-80 was selected as the dispersant for hydrogenation experiment. XRD is a common method for qualitative analysis of substances and crystal structure analysis. The crystal structure and size of the loaded Pt particles were analyzed by XRD on C60 / Pt (abbreviated as C60 / Pt+) with 0.25% Tween-80 added and C60 / Pt without dispersant added. The results are as follows: Figure 7 shown.
[0069] The XRD patterns of the two catalysts showed diffraction peaks at 10.81°, 17.70°, 20.79° and 21.72°. By comparing with the standard phase card, it was found that they were characteristic peaks of C60, which showed that after adding the dispersant, the catalyst retained the inherent crystal structure of the carrier, and the addition of the dispersant did not affect the crystal structure of the carrier, which was consistent with the research results of Yue et al. In addition, there were also differences between the two catalysts. The XRD pattern of C60 / Pt+ showed diffraction peaks at 39.76°, 46.24°, 67.45°, 81.29° and 85.71°. By comparing with the standard phase card, it was found that they corresponded to the 111, 200, 220, 311 and 222 crystal planes of Pt, respectively, indicating that the Pt particles were well crystallized on the carrier surface during the loading process; the peak at 39.76° was sharp, indicating that the 111 crystal plane was dominant in the Pt crystal. The 111 crystal plane represented by 39.76° in C60 / Pt+ is sharper, which indicates that the addition of dispersant has a significant effect on the crystallization state of Pt material on the catalyst surface. The diffraction peak intensity of the catalyst with dispersant increased and the crystallinity improved, which is consistent with Wang's research.
[0070] The peak information in the XRD spectrum was analyzed by software to obtain information such as FWHM and 2θ. The crystal size was calculated according to the Scherrer equation. The results are shown in Table 1.
[0071] Table 1 C60 / Pt and C60 / Pt + Pt particle size in the catalyst
[0072]
[0073] It can be seen from Table 1 that the thickness of the Pt particles in the 111 crystal plane direction in Pt / C60 is approximately Pt / C60 + The thickness of the 111 crystal plane of the Pt particle is about The crystal size becomes smaller, which may be due to the addition of dispersant making Pt more dispersed.
[0074] 5. Determination of platinum content in catalyst
[0075] Chemical analysis is based on the relationship between Pt and SnCl 2 The principle of color development is to determine and calculate the Pt content in the catalyst through the linear relationship between absorbance and concentration. The Pt concentration and absorbance standard curve is established by using Pt standard solutions with different concentration gradients. The related equation y=11.94x+0.1525, R2=0.9984 is obtained through linear fitting. The results are as follows Figure 8 shown.
[0076] By measuring the Pt / C60 catalyst and SnCl 2 The absorbance value after the reaction was calculated according to the fitting equation to obtain the Pt content, and the error was detected using a chloroplatinic acid solution of known concentration, and the results are shown in Table 2. The measurement results show that the Pt loading in the Pt / C60 catalyst is 20.07%, indicating that the Pt loading of the Pt-based catalyst with C60 as the carrier prepared by the liquid phase reduction method is not high, which may be because the C60 particle size is too small and its surface activation energy is high. After agglomeration, its specific surface area is reduced, and the active sites that can provide Pt are correspondingly reduced, so the catalyst loading of platinum is not high. Compared with the actual Pt concentration and nominal value of chloroplatinic acid, it can be found that its relative error is 0.3%, indicating that the relative error of the platinum content measured by this method is small.
[0077] Table 2 Results of determination of platinum content in Pt / C60 catalyst and chloroplatinic acid
[0078]
[0079] Note: “—” means not present or not detected.
[0080] 6. Analysis of catalyst activity
[0081] During the reaction, the catalyst can change the activation energy of the reaction, and thus change the rate of the chemical reaction. This effect is called catalysis. The strength of the catalytic activity is the key to changing the reaction rate. When the catalytic effect is strong, it can better promote the chemical reaction. Under the same hydrogenation conditions of 50℃ and normal pressure, the water phase flow rate is set to 35mL / min, the oil phase flow rate is 50mL / min, and the anode catalyst is RuO 2 , loading is 0.6mg / cm 2 The cathode catalyst C60 / Pt loading is 0.4 mg / cm 2 (in terms of Pt), constant current charging 500mA, using C60 / Pt catalyst and C60 / Pt + The relationship between LnIv and time of hydrogenation of soybean oil by catalyst is as follows Fig. 9 The results show that after 2 hours of hydrogenation, at the same time, the iodine value of the hydrogenated oil catalyzed by C60 / Pt is higher than that of C60 / Pt +The iodine value of the hydrogenated oil obtained. According to the relationship between the hydrogenation reaction rate constant and the iodine value, there is a linear relationship between LnIv and the hydrogenation time, and its slope kC H The size of the catalytic activity can be reflected, indicating that C60 / Pt + Has better catalytic activity.
[0082] 2. Optimization of SPE hydrogenation process with dispersant addition
[0083] Through single factor experiments, the amount of Pt / C60 catalyst in MEA, the core component of the SPE electrochemical hydrogenation reaction device, the hydrogenation temperature in the soybean oil hydrogenation process, and the process conditions of oil phase flow rate were optimized according to the changes in resistance and iodine value, and the changes in fatty acid composition over time under this process were analyzed. The external electric field was applied by the BTS high-precision battery detection system, with a constant current of 500mA and a maximum voltage of 5000mV.
[0084] 1. Effect of catalyst dosage on hydrogenation process and products
[0085] MEA is a key component of the SPE hydrogenation reactor and is the main site for oil hydrogenation reaction. Its structural composition includes spraying with RuO 2 The anode carbon paper, cathode carbon paper of C60 / Pt and Nafion117 proton exchange membrane are used. Therefore, the amount of catalyst in MEA is closely related to the resistance, MEA life and product quality during hydrogenation. The SPE hydrogenation reaction device was used at 60°C and atmospheric pressure, with the water phase flow rate set to 35 mL / min, the oil phase flow rate set to 50 mL / min, and the anode catalyst set to RuO 2 , loading is 0.6mg / cm 2 , the optimal dosage of cathode catalyst Pt / C60 (0.1-0.6 mg / cm2 in terms of Pt) under constant current charging of 500 mA 2 ) for exploration.
[0086] Fig.10 The following is a curve showing the change of iodine value corresponding to different catalyst dosages. It can be seen that the amount of cathode C60 / Pt required for electrohydrogenation has a great influence on the iodine value of hydrogenated oils. 2 Increased to 0.4 mg / cm 2 The iodine value of hydrogenated oil tends to decrease when the catalyst content is low. This is because when the catalyst content is low, the metal-hydrogen and metal-double bond complexes formed are low. Therefore, increasing the amount of catalyst will significantly increase the rate of hydrogenation reaction. 2When the amount of catalyst increases, the iodine value of hydrogenated oil tends to change slowly, indicating that further increase in the amount of catalyst does not have a significant effect on the iodine value of hydrogenated oil. This may be because the catalyst cannot completely contact with the oil on a fixed carbon paper size, resulting in a limited catalytic surface area for the reaction. Therefore, when the catalyst reaches a certain amount, the catalytic efficiency is no longer improved.
[0087] The resistance values measured in the experiment are all the resistance at 10 minutes of hydrogenation reaction, because at this time the MEA will not be damaged by the reaction, the hydrogenation reaction is relatively stable, and can reflect the resistance situation under the same conditions. Fig.11 The effect of different catalyst dosages on the resistance during hydrogenation. As can be seen from the figure, with the increase of catalyst dosage, the resistance shows a downward trend. 2 Increased to 0.4 mg / cm 2 When the amount of catalyst is 0.4mg / cm2, the resistance of the hydrogenated oil shows a large drop, which is consistent with the change trend of the iodine value of the hydrogenated oil. Therefore, considering the effect of different catalyst dosages on the iodine value of the hydrogenated oil and the hydrogenation resistance, the optimal catalyst dosage is 0.4mg / cm2. 2 .
[0088] 2. Effect of hydrogenation temperature on hydrogenation process and products
[0089] The rate of chemical reactions is affected by the ambient temperature. It is generally believed that the reaction rate increases by 2 to 4 times for every 10K increase in temperature. The hydrogenation reaction of oils and fats is essentially an addition reaction, so the hydrogenation temperature has a significant effect on the SPE hydrogenation process. Under normal pressure conditions, the water phase flow rate is set to 35 mL / min, the oil phase flow rate is 50 mL / min, and the anode catalyst is RuO 2 , loading is 0.6mg / cm 2 The cathode catalyst C60 / Pt loading is 0.4 mg / cm 2 (in terms of Pt), constant current charging 500mA, and the effect of reaction temperature on the hydrogenation process was explored by changing the hydrogenation temperature (30-80°C).
[0090] Fig.12 The iodine value of hydrogenated oil corresponding to different hydrogenation temperatures is shown. It can be seen that when the temperature rises from 30°C to 50°C, the iodine value of hydrogenated oil gradually decreases, indicating that the increase in temperature is conducive to the hydrogenation reaction. When the temperature rises, it is conducive to increasing the dissolution of hydrogen in oils and fats, and at the same time it can reduce the viscosity of oils and fats, making it easier for hydrogen to combine with oils for addition reaction, thereby improving the progress of hydrogenation reaction. When the reaction temperature rises from 50°C to 80°C, the iodine value of the corresponding hydrogenated oil increases and tends to be stable. This may be because with the increase in temperature, the damage of the membrane electrode MEA is accelerated, resulting in a decrease in hydrogenation efficiency and an increase in the iodine value.
[0091] Depend on Fig.13 It can be seen that when the reaction temperature is between 30 and 70 °C, the resistance shows a trend of first decreasing and then increasing. When the temperature is 40 °C, the resistance value is the smallest, which is 3.96Ω. When the hydrogenation reaction temperature is higher than 70 °C, the resistance tends to be stable. This may be related to the carbon-based material as a membrane electrode and the H protons produced during the reaction. The resistance of the carbon-based material decreases linearly with the increase of temperature. The increase in temperature can increase the concentration of H protons on the catalyst surface in the hydrogenation reaction system. When the reaction temperature is 30 °C and 40 °C, the H protons produced are not enough to dominate the change in resistance; when the temperature is higher than 40 °C, the concentration of H protons increases with the increase in temperature, resulting in an increase in resistance. Therefore, considering the effects of different catalyst dosages on the iodine value of hydrogenated oil and the size of hydrogenation resistance, the optimal hydrogenation reaction temperature is selected as 50 °C.
[0092] 3. Effect of oil phase flow rate on hydrogenation process and products
[0093] The SPE electrochemical hydrogenation reaction process can be divided into two parts: the water at the anode generates H protons under electrolysis, and H enters and reacts with the carbon-carbon double bond. Due to the different reaction energy barriers of the two, there is a certain rate difference, so the appropriate oil phase flow rate has a significant effect on the concentration of H protons in the anode chamber and the adsorption of the catalyst layer and the oil phase. Under 50℃ and normal pressure conditions, the water phase flow rate is set to 35mL / min, and the anode catalyst is RuO 2 , loading is 0.6mg / cm 2 The cathode catalyst C60 / Pt loading is 0.4 mg / cm 2 (in terms of Pt), constant current charging was 500mA, and the oil phase flow rate was set to 20-70mL / min, respectively, to explore the effect of the flow rate on the hydrogenation results.
[0094] like Fig.14 As shown in the figure, when the oil phase flow rate increases from 20 to 50 mL / min, the iodine value of the hydrogenated oil obtained shows a trend of gradual decrease. This may be because as the oil phase flow rate increases, the soybean oil in the oil phase can more fully react with the H protons generated by the electrohydrogenation device, thereby reducing the iodine value. When the oil phase flow rate is 60 mL and 70 mL / min, the iodine value of the corresponding hydrogenated oil is low, 119 g / 100 g and 123 g / 100 g, respectively. This shows that too large a flow rate is not conducive to the hydrogenation reaction. It may be due to the increase in flow rate. The excessively high flow rate takes away the H protons that pass through the Nafion membrane, which reduces the H proton concentration in the cathode chamber, and the amount of H protons participating in the hydrogenation reaction is insufficient, affecting the reaction rate. From the comparison of the hydrogenated oil obtained after the reaction, it can also be clearly found that the turbidity caused by hydrogenation of the hydrogenated oil with a large oil phase flow rate is also significantly lower than that at other temperatures.
[0095] Fig.15 The figure shows the effect of different oil phase flow rates on hydrogenation resistance, and the resistance is the resistance when the hydrogenation reaction lasts for 10 minutes. When the oil phase flow rate is from 20 to 70 ml / min, the hydrogenation resistance shows a trend of first rising and then falling. This may be because as the oil phase flow rate increases, the excessive flow rate takes away the H protons that pass through the Nafion membrane, causing the membrane electrode hydrogen proton concentration to decrease and the resistance to gradually decrease. Therefore, considering the effect of different catalyst dosages on the iodine value of hydrogenated oil and the size of hydrogenation resistance, the optimal oil phase flow rate is 40 ml / min.
[0096] 4. Effect of time on hydrogenation process and products
[0097] Based on the above optimization scheme, the effect of time on the hydrogenation process and products was studied. Under normal pressure at 50°C, the water phase flow rate was set to 35 mL / min, the oil phase flow rate was set to 40 mL / min, and the anode catalyst was RuO 2 , loading is 0.6mg / cm 2 The cathode catalyst C60 / Pt loading is 0.4 mg / cm 2 (measured in Pt), constant current charging 500mA.
[0098] Fig.16 The figure shows the effect of different hydrogenation times on the iodine value of hydrogenated oil. It can be clearly seen that with the extension of hydrogenation time, the iodine value of the corresponding soybean hydrogenated oil shows a gradual downward trend. During the experiment, when the hydrogenation reaction just started, the amount of unsaturated fatty acids contained in the soybean oil was high, the reaction substrate in the reaction system was sufficient, and the hydrogenation reaction could proceed smoothly and quickly. When the reaction was over, the iodine value of the hydrogenated oil was about 110, which was slightly hydrogenated, indicating that it still contained some unsaturated fatty acids and the hydrogenation reaction was not affected. Therefore, during the entire hydrogenation process, the iodine value of the hydrogenated oil showed a straight downward trend.
[0099] Table 3 Fatty acid composition of soybean oil sampled every 30 minutes during hydrogenation
[0100]
[0101] Note: In the table, inconsistent letters in the data columns marked with letters represent significant differences (p<0.05), identical letters represent no significant differences (p<0.05), and SD=0.00 represents an error less than 0.01.
[0102] Table 3 shows the fatty acid composition of samples taken every 30 minutes during the hydrogenation of soybean oil, and the results are the same as expected. The content of linoleic acid and linolenic acid gradually decreases with time, the content of oleic acid increases slightly with time, and the content of stearic acid increases gradually with time, which indicates that the unsaturated double bonds are saturated by hydrogenation in the SPE reactor during the hydrogenation process. The increase in oleic acid content is consistent with the oil hydrogenation theory proposed by Ai Hongtao et al. (i.e., trienoic acid is hydrogenated to form dienoic acid during hydrogenation, dienoic acid and newly generated dienoic acid are hydrogenated to form monoenoic acid, and monoenoic acid and newly generated monoenoic acid generate saturated enoic acid), indicating that new dienoic acid is generated during the hydrogenation process. It can be seen from the data in Table 3 that the linoleic acid content has changed significantly, indicating that linoleic acid is the main reaction during the hydrogenation of soybean oil, probably because the content of linoleic acid accounts for a large proportion, and the probability of collision with the catalytic active center is greater, so the degree of reaction is higher. The content of other components has changed little, which is also consistent with the research results of Xiao Feiyan et al.
[0103] 3. SPE hydrogenated soybean oil quality analysis
[0104] Soybean oil was hydrogenated by SPE electrochemical hydrogenation reactor at 50°C under normal pressure. The oil phase flow rate was 50 mL / min, the water phase flow rate was 35 mL / min, and the anode catalyst was RuO 2 (0.6mg / cm 2 ), the cathode catalysts were C60 / Pt and C60 / Pt with 0.25% Tween-80 added, with a loading of 0.4 mg / cm 2 (Pt-based). The fatty acid composition, trans fatty acid content, oil crystallization and melting curves, crystal morphology and flavor of hydrogenated soybean oil after 2 hours of reaction were analyzed to explore the relationship between the catalytic performance of the two catalysts and the quality of the hydrogenated products.
[0105] 1. Analysis of basic indicators of SPE hydrogenated soybean oil
[0106] Table 4 Quality analysis of soybean oil, C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil
[0107]
[0108] Depend on Fig.17It can be seen that the color of the oil after hydrogenation changes significantly, from yellow transparent before hydrogenation to beige; Table 4 shows the basic index quality analysis of soybean oil, C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil. The smells are similar, both of which have a light bean fragrance. The iodine value and refractive index of soybean oil after hydrogenation have decreased, which is consistent with the results of Ihsan et al. The peroxide value of soybean oil after hydrogenation has decreased, and the acid value has increased but is still at a low value, indicating that C60 / Pt+ is feasible to be used as a catalyst in the SPE reactor, and the prepared hydrogenated product is of good quality.
[0109] 2. Analysis of fatty acid composition of hydrogenated soybean oil by SPE
[0110] Table 5 shows the fatty acid composition of soybean oil and two hydrogenated oils obtained by gas chromatography. The results show that the main components of soybean oil are palmitic acid, oleic acid and linoleic acid, accounting for 84.91% of the total components, of which linoleic acid accounts for the largest proportion, 53.77%, which is consistent with the research results of Chen Xia et al. As can be seen from Table 5, compared with soybean oil, the content of oleic acid and stearic acid in the two hydrogenated oils has increased, the content of linoleic acid and linolenic acid has decreased, and the content of other components has not changed much. This change is in line with the oil hydrogenation theory proposed by Ai Hongtao, that is, during the hydrogenation process, trienoic acid is hydrogenated to form dienoic acid, dienoic acid and newly generated dienoic acid are hydrogenated to form monoenoic acid, and monoenoic acid and newly generated monoenoic acid are formed into saturated enoic acid. The content of other components has changed little, which is consistent with the research results of Xiao Feiyan et al. Compared with C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil, C60 / Pt+ hydrogenated oil has lower linoleic acid content and higher stearic acid content, indicating that the addition of dispersant can improve the hydrogenation efficiency of oil, which is consistent with the catalytic activity results of the catalyst.
[0111] Table 5 Fatty acid composition of soybean oil and hydrogenated soybean oil
[0112]
[0113] 3. Analysis of trans fatty acid content in hydrogenated soybean oil by SPE
[0114] Table 6 Trans fatty acid content in soybean oil and hydrogenated soybean oil
[0115]
[0116] Table 6 shows the trans fatty acid content of soybean oil and two hydrogenated oils obtained by gas chromatography. After SPE hydrogenation, the total trans fatty acid content of the two hydrogenated oils increased, among which the increase was more prominent in C 18:1n9t and C 18:3n9t,12c,15t, indicating that there is an isomerization reaction during the hydrogenation process. Compared with the 5.28% trans fatty acid content obtained by traditional hydrogenation studied by Karabulut et al., the trans fatty acid content in the hydrogenated oil obtained by this hydrogenation method is lower. This is mainly related to the fact that SPE oil hydrogenation can carry out oil hydrogenation reaction at a lower temperature. Traditional hydrogenation requires a high temperature of up to 220°C in an intermittent reactor, while the temperature set for the SPE reactor of the present invention is 50°C. Li An used Gussian software to simulate the path of the isomerization reaction of soybean oil through density functional theory and found that ambient temperature is a key factor affecting the formation of unsaturated fatty acids. The calculation results show that the isomerization of a single cis double bond needs to overcome a reaction energy barrier greater than 200kJ / mol to form a transition state, and higher temperatures are conducive to this process. Compared with the C in the two hydrogenated oils, 18:3n9c,12c,15t , C 18:3n9tc12t,15c and C 18:3n9t,12c,15t It can be found that C60 / Pt+ hydrogenated oil has a slightly lower trans fatty acid content, which may be related to the fact that the addition of dispersants improves the catalytic efficiency of the catalyst. The generation of trans fatty acids is related to the diffusion and transfer efficiency of H protons and their utilization rate. Insufficient H protons will lead to the generation of more TFAs. Due to the addition of dispersants, everything from the catalyst carrier to the Pt loaded on the catalyst is dispersed more evenly under the influence of the dispersant, allowing the catalyst C60 / Pt+ and soybean oil to undergo hydrogenation reactions more effectively and quickly, reducing the occurrence of isomerization.
[0117] 4. SPE hydrogenation current efficiency analysis
[0118] Table 7 C60 / Pt and C60 / Pt+ hydrogenation current efficiency
[0119]
[0120] The current efficiency (CE) of oil hydrogenation is a quantitative analysis method for evaluating the efficiency of electrochemically generated hydrogen and the addition of oil double bonds. CE can directly reflect the activity of the catalyst, that is, the larger the CE, the stronger the activity of the catalyst. As shown in Table 7, the current efficiency of hydrogenation of C60 / Pt and C60 / Pt+ are 53.42% and 70.84%, respectively, indicating that the catalytic activity of C60 / Pt+ is higher than that of C60 / Pt, which is consistent with the results of catalyst activity analysis. This may be because the addition of dispersant inhibits the agglomeration of the catalyst carrier and also inhibits the agglomeration of Pt during the hydrogenation process, so that the catalyst has a larger specific surface area, and the Pt particles loaded on C60 become smaller, which improves the catalytic activity of the catalyst, and then makes the current efficiency of C60 / Pt+ greater than that of C60 / Pt. The high CE of SPE electrochemical hydrogenation method is mainly attributed to the large reaction area of oil / water / catalyst, and the protons and electrons in the cathode catalyst layer can react with oil efficiently. The main reason why CE is less than 100% is that during the flow of current, the electroosmotic resistance between water and migrating protons causes water to be retained at the cathode end of the SPE hydrogenation device, the catalytic sites are covered by water, and some electrochemically generated hydrogen leaves the cathode end in the form of bubbles and does not participate in the hydrogenation reaction.
[0121] 5. SPE hydrogenation selectivity analysis
[0122] Table 8 Hydrogenation selectivity of fatty acids
[0123]
[0124] Table 8 shows the results of hydrogenation selectivity calculated by Matlab for C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil. The hydrogenation selectivity of the catalyst with dispersant added and without dispersant added is similar, and SLn is the largest, indicating that the reaction rate of hydrogenation of linolenic acid to linoleic acid is greater during the hydrogenation reaction. In their study on the hydrogenation process of soybean oil, Sun et al. showed that a higher linolenic acid content would affect the flavor stability of the hydrogenated product, so a catalyst with a higher SLn has better commercial value. At the same time, SLn can intuitively reflect the hydrogen concentration in the reaction system. A higher hydrogen concentration in the reaction system reduces SLn, indicating that C60 / Pt+ can better adsorb H protons for reaction, which is conducive to improving catalytic efficiency and reducing the formation of TFAs. The linoleic acid hydrogenation selectivity (SLo) of the two hydrogenated oils is the lowest in the same group. This may be because while trienoic acid generates dienoic acid, the newly generated dienoic acid and the inherent dienoic acid are also generating monoenoic acid, and the content of dienoic acid in the total component does not change much.
[0125] 6. SPE hydrogenated soybean oil flavor analysis
[0126] The analysis results of soybean oil, C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil are as follows: Fig.18 As shown. Through the electronic nose radar chart, it can be found that the aroma components of soybean oil are mainly dominated by sensors 2 and 6, corresponding to nitrogen oxides and alkanes, respectively. Sensors 1, 3, 4, 5, 7 and 9 also have certain response values, corresponding to aromatic compounds, ammonia aromatic substances, hydrides, olefins, aromatic groups, polar molecules, sulfur compounds and aromatic compounds, sulfur organic compounds, indicating that these substances also contribute to the flavor of soybean oil. The flavor components of the two hydrogenated oils are mainly sensors 2, 4 and 6, with high response values, indicating that the flavor analysis results of the two hydrogenated oils are relatively similar. Compared with soybean oil, the response values of sensors 2, 4 and 6 increased significantly after hydrogenation, indicating that nitrogen oxides, hydrides and alkanes increased after hydrogenation.
[0127] The multivariate data of the 10 sensors of the electronic nose were processed by principal component analysis (PCA) in the Airsense software. The PCA analysis results of the three samples are shown in Fig.19 As shown. The analysis results show that after PCA processing, the multivariate data is transformed into two principal components PC-1 (78.18%) and PC-2 (18.77%), and the flavor contribution rate of the two is as high as 96.95%, indicating that the two principal components basically represent the main information characteristics of the samples. According to the PCA analysis results, it can be found that among the three samples, only soybean oil and C60 / Pt+ hydrogenated oil have a slight cross phenomenon, indicating that there are certain differences in the flavors of the three samples.
[0128] 7. Analysis of melting and crystallization curve of SPE hydrogenated soybean oil
[0129] Differential scanning calorimetry is a thermal analysis method that measures the relationship between the power difference (such as heat flow) input to the sample and the reference under programmed temperature control and the temperature. The differential scanning calorimeter can analyze the crystallization changes of the sample under non-isothermal conditions. The recorded changes can be analyzed to obtain the non-isothermal crystallization curve, which is used to analyze a variety of thermodynamic and kinetic parameters.
[0130] like Fig. 20 The melting and crystallization curves are shown in Figure 1, where A, B and C are soybean oil, C60 / Pt hydrogenated oil and C60 / Pt respectively. + Melting and crystallization curves of hydrogenated oils. As can be seen from the figure, these three oils all have a relatively wide melting peak, which indicates that these three oils have a relatively wide melting point range. Comparing the melting peaks of C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil with soybean oil, it can be found that the melting peaks of the two hydrogenated oils are relatively widened to the left relative to soybean oil, indicating that oil hydrogenation can change its melting point range to a certain extent.+ Compared with the melting peak of hydrogenated oil, C60 / Pt+ has a broader melting peak, indicating that under the same conditions, C60 / Pt + The hydrogenated oil obtained from C60 / Pt has a higher degree of hydrogenation. The crystallization curves also have similar results. + The crystallization peak of hydrogenated oil is also broader than that of soybean oil. The two hydrogenated oils show the same trend: the crystallization peak of hydrogenated oils also becomes broader.
[0131] Table 9 Melting curve parameters
[0132]
[0133] Table 10 Crystallization curve parameters
[0134]
[0135] Tables 9 and 10 show the starting temperature, peak value, ending temperature and enthalpy of the melting peak and crystallization peak. Compared with C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil, the starting temperature, peak value and ending temperature of the melting peak of soybean oil are all shifted to the left, and the melting enthalpy is also increased; the starting temperature, peak value and ending temperature of the crystallization peak are all shifted to the right, and the crystallization enthalpy is also decreased. This shows that hydrogenation increases the melting point of the sample, and the greater the energy value required for the melting process. This is mainly because hydrogenation makes the fatty acids arranged on the triglycerides in soybean oil more and more saturated, and as the degree of saturation increases, the structure changes, the molecular bond force is strengthened, and the molecular potential energy increases, so more energy is required to destroy this force during the melting process. Comparing the melting and crystallization peaks of C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil, C60 / Pt+ hydrogenated oil has a slightly higher melting enthalpy and a slightly lower crystallization enthalpy, indicating that the melting point of C60 / Pt+ hydrogenated oil is slightly higher than that of C60 / Pt hydrogenated oil.
[0136] 8. SPE hydrogenated soybean oil crystal morphology analysis
[0137] After hydrogenation, the unsaturation level of vegetable oil decreases, and the melting point changes accordingly, resulting in crystallization at room temperature. After fat crystallization, it has a certain crystalline morphology and microscopic network structure, and its crystal size is usually 1 to 140nm. The crystallization of fats can usually be divided into two processes: the formation of crystal nuclei and the growth of crystals. When the temperature is lower than the melting point of the fat, under the driving force of supercooling conditions, the triglyceride molecules gradually change from a disordered state to an ordered arrangement, forming a crystal core, and the crystal core is regularly arranged and continuously grows to form crystals.
[0138] Fig.21The crystallization images of soybean oil and hydrogenated oil observed under polarized light microscope after sampling under the same conditions and refrigerating for 1 hour are shown. Through microscopic imaging observation, it can be found that no crystallization is found in soybean oil, while the two hydrogenated oils show different degrees of crystallization. This shows that the saturation and melting point of soybean oil after hydrogenation treatment are improved, and crystallization occurs at room temperature. At the same time, it can be found that there are differences in the crystallization state of hydrogenated oils prepared by C60 / Pt+ and C60 / Pt. The crystal distribution of hydrogenated oil prepared by C60 / Pt+ is relatively tight and the crystal size is large, while the distribution of hydrogenated oil prepared by C60 / Pt is relatively loose and the crystal size is small. This may be because in the same short crystallization time, the hydrogenated oil prepared by C60 / Pt+ has a faster crystallization rate and a higher degree of crystallization. This is consistent with the DSC results. The hydrogenated oil prepared by C60 / Pt+ has a smaller crystallization enthalpy, and the same mass of hydrogenated oil needs to release less energy.
[0139] IV. Conclusion
[0140] The present invention disperses soccer ball-shaped fullerene C60 with 0.25% Tween-80 and uses it as a carrier to prepare C60 / Pt catalyst. The SPE electrochemical hydrogenation reactor is used to study the hydrogenation process of soybean oil under low temperature and normal pressure conditions, and the quality, flavor and physical properties of hydrogenated soybean oil are explored. The main conclusions are as follows:
[0141] (1) The different mass fractions of different dispersants added to C60 / Pt were optimized through sedimentation experiments. The sedimentation stability coefficients of C60 / Pt without dispersant were 0.83, 0.75, 0.67 and 0.6 at 12h, 24h, 36h and 48h, respectively. The optimal mass fraction of Tween-80 dispersant added to C60 / Pt was 0.25%, and the sedimentation stability coefficients at 12h, 24h, 36h and 48h were 0.86, 0.83, 0.8 and 0.8, respectively. The optimal mass fraction of polyethylene glycol-6000 dispersant added to C60 / Pt was 0.05%, and the sedimentation stability coefficients at 12h, 24h, 36h and 48h were 0.86, 0.8, 0.75 and 0.75, respectively. Comparing the optimal dosages of Tween-80 and polyethylene glycol-6000, 0.25% Tween-80 has a better dispersion effect.
[0142] (2) The results of particle size and potential analysis show that different mass fractions of different dispersants have different effects on the particle size and potential of the catalyst. The average particle size of C60 / Pt without dispersant is 177.2nm, and the average particle sizes of C60 / Pt with 0.05%, 0.25% and 1% Tween-80 are 204.3nm, 158.6nm and 217nm respectively; the average particle sizes of C60 / Pt with 0.05%, 0.25% and 1% polyethylene glycol-6000 are 152.9nm, 170.4nm and 298.6nm respectively. The potential of C60 / Pt without dispersant is -20.3mV, while the potentials of C60 / Pt with 0.05%, 0.25% and 1% Tween-80 are -43.5mV, -9.69mV and -15.5mV respectively; the potentials of C60 / Pt with 0.05%, 0.25% and 1% polyethylene glycol-6000 are -13.8mV, -14.1mV and -29.3mV respectively. Comparing Tween-80 and polyethylene glycol-6000, Tween-80 can obtain a potential of -43.5mV. According to the fact that the larger the potential, the more stable the solution system is, it is determined that Tween-80 has a better effect; TEM analysis results show that the addition of dispersant makes the dispersant wrapped on the surface of C60, and the Pt loaded on C60 also becomes more uniform due to the addition of dispersant.
[0143] (3) XRD analysis results show that the morphology and structure of C60 / Pt with 0.25% Tween-80 added are good. Compared with the characteristic peaks in the standard material card, it is found that the structure of C60 has not changed due to the addition of dispersant. The characteristic peaks of Pt in C60 / Pt after adding dispersant also become sharper, indicating that the crystallinity of Pt particles is good. There are 111, 200, 220, and 311 crystal planes, among which 111 crystal plane is the main one. The crystal size of 111 crystal plane is calculated according to the Scherrer equation, and the size of Pt in C60 / Pt is (9.58nm); the size of Pt in C60 / Pt+ is (6.78nm), and the Pt particles in the catalyst also become smaller due to the addition of dispersant.
[0144] (4) The Pt content in the catalyst was determined to be 20.07% for C60. The results of the test with chloroplatinic acid solution showed that the nominal value of chloroplatinic acid was 0.0312 mg / ml, the actual Pt concentration was 0.0311 mg / ml, and the relative error was 0.3%. The catalyst activity results showed that the linear relationship between the LnIv of C60 / Pt and the hydrogenation time was kC H The linear relationship between LnIv of C60 / Pt+ and hydrogenation time is -0.0011; kC HIt is -0.0015. According to the smaller the slope, the higher the catalytic activity, C60 / Pt dispersed with 0.25% Tween-80 has higher catalytic activity; the current efficiency calculated according to the formula shows that the current efficiency of C60 / Pt+ is 71.22%; the current efficiency of C60 / Pt is 53.42%, and C60 / Pt+ has better catalytic efficiency.
[0145] (5) When C60 / Pt+ was used as the SPE cathode catalyst for soybean oil hydrogenation, the optimal reaction conditions were: reaction temperature 50 °C, oil phase flow rate 50 mL / min, water phase flow rate 35 mL / min, cathode catalyst loading 0.4 mg / cm 2 , the anode catalyst is RuO 2 (0.6mg / cm 2 ). The fatty acid composition under different hydrogenation times was obtained by gas chromatography. The results showed that the contents of linoleic acid and linolenic acid gradually decreased with the increase of hydrogenation time; the content of stearic acid gradually increased with the hydrogenation time; the content of oleic acid slightly increased with the hydrogenation time, and the contents of other components remained almost unchanged, which was consistent with the oil hydrogenation theory proposed by Ai Hongtao et al.
[0146] (6) Fatty acid composition analysis showed that the unsaturated double bonds in octadecanoic acid reacted during the hydrogenation of soybean oil. After hydrogenation, the contents of linoleic acid and linolenic acid decreased, while the contents of oleic acid and stearic acid increased. Compared with C60 / Pt hydrogenated oil, C60 / Pt+ hydrogenated oil had higher oleic acid (22.4%) and stearic acid (11.91%) contents. The TFAs content in C60 / Pt+ hydrogenated oil was only 1.5% (110 g I 2 / 100g), which is lower than that in C60 / Pt hydrogenated oil (1.61%, 113g I 2 / 100g); In the hydrogenation reaction, the SLn of both catalysts was the largest and the SLo was the smallest, and the SLn of C60 / Pt+ was lower than that of C60 / Pt, indicating that the H proton concentration on its surface was higher, which was beneficial to improve the catalytic efficiency and reduce the formation of TFAs.
[0147] (7) The response values of nitrogen oxides and alkanes in soybean oil flavor are the most obvious, and aromatic compounds, ammonia aromatic substances, hydrides, olefins, aromatics, polar molecules, sulfur compounds and aromatic compounds, and sulfur organic compounds also have certain response values. The response value of hydrides increased after hydrogenation, indicating that the flavor components have changed, while the flavor radar charts of C60 / Pt and C60 / Pt+ are relatively similar, only the response value of nitrogen oxides of C60 / Pt+ is slightly lower. The PCA analysis chart has good discrimination between the two hydrogenated oils, and there is no crossover phenomenon.
[0148] (8)DSC results show that the melting peak and crystallization peak of hydrogenated oil become broader after hydrogenation treatment. The melting and crystallization curve parameters obtained by Origin treatment are as follows: the melting peak temperatures of soybean oil, C60 / Pt hydrogenated oil and C60 / Pt+ hydrogenated oil are -27.5°C, -28.7°C and -28.3°C, respectively; the melting start temperatures are -4.5°C, -8.9°C and -9.4°C, respectively; the melting end temperatures are 6.2°C, 4.3°C and -12.8°C, respectively; and the melting enthalpies are 362.12 J·g -1 、391.33J·g -1 and 392.71 J·g -1 The crystallization peak temperatures are -17.4°C, -10.3°C and -9.9°C, respectively; the crystallization starting temperatures are -12.9°C, -6.9°C and -5.4°C, respectively; the crystallization ending temperatures are 6.7°C, 5.6°C and 5.1°C, respectively; the crystallization enthalpy is 63.24 J·g -1 , 7.29 J·g -1 and 5.91 J·g -1 C60 / Pt+ hydrogenated oil has higher melting enthalpy and lower crystallization enthalpy.
[0149] (9) Soybean oil is golden in color, clear and transparent, but becomes viscous off-white and opaque after hydrogenation. Microscopic analysis shows that there are obvious oil crystals in hydrogenated oil. The crystals of C60 / Pt+ hydrogenated oil are more uniform, while the crystal states of C60 / Pt hydrogenated oil are different. Hydrogenated oil has changes in refractive index, acid value, peroxide value, etc.
Claims
1. A method for chemically modifying a fullerene C60 carrier, characterized in that The method comprises the following steps: Weigh 5-15 mg of C60 / Pt catalyst, place it in a centrifuge tube, add 5-15 mg of isopropanol; add dispersant Tween 80, ultrasonic treatment for 5-15 minutes, add binder, and continue ultrasonic treatment for 40-60 minutes. After the ultrasonic treatment, let it stand for 12-48 hours to obtain a chemically modified fullerene C60 / Pt catalyst, wherein: the amount of the dispersant added is 0.25% of the mass of the chemically modified fullerene C60 / Pt catalyst, and the amount of the binder added is 5-40% of the mass of the chemically modified fullerene C60 / Pt catalyst. The preparation method of the C60 / Pt catalyst is as follows: (1) Purification and oxidation of fullerenes Take 4-6 g of fullerene sample, mix it evenly with 2.0-3.0 g of NaNO3, add 100-150 mL of concentrated H2SO4, stir in an ice bath for 60-120 min, then slowly add 10-20 g of KMnO4, remove the ice bath and stir for 30-60 min; after the reaction is complete, slowly add the obtained slurry into 200-250 mL of ultrapure water, control the temperature to 80-100 °C, stir evenly for 0.5-1.5 h, and then make up to 700 mL with 3% H2O2 solution and warm water; wash it several times with 30% v / v HCl, filter it and get a slurry, dry it in a vacuum drying oven at 60-80 °C for 1-3 h to get oxidized C60; (2) Preparation of C60 / Pt catalyst by liquid phase reduction method Take 50-55 mg of oxidized C60 and add it to 200-250 mL of ultrapure water, and ultrasonically treat it for 30-90 min to obtain a catalyst carrier suspension; then add 5-15 mL of 0.01-0.05 mol / L H2PtCl6 solution while stirring, and adjust the pH to 11-12 with 0.5-1.5 mol / L NaOH; add 1-3 g of NaBH4 to the liquid phase, and stir at room temperature for 25-30 h. After the reaction is completed, wash with ultrapure water until the pH value is neutral, and filter it. The obtained slurry is dried in a vacuum drying oven at 60-80°C for 1-3 h to obtain a fullerene C60 loaded with Pt catalyst.
2. The method for chemically modifying a fullerene C60 carrier according to claim 1, characterized in that The adhesive is a mixture of polytetrafluoroethylene emulsion and Nafion solution, the mass ratio of polytetrafluoroethylene to Nafion solution is 1:1, the mass concentration of polytetrafluoroethylene emulsion is 5-40%, and the mass concentration of Nafion solution is 5-40%.
3. The method for chemically modifying a fullerene C60 carrier according to claim 1, characterized in that The particle size of the fullerene is 20-400 nm, and the Pt content in the C60 / Pt catalyst is 10-90%.
4. Use of the chemically modified fullerene C60 / Pt catalyst prepared by the method according to any one of claims 1 to 3 as a cathode catalyst in a SPE electrochemical hydrogenation reactor.
5. Use of a chemically modified fullerene C60 / Pt catalyst prepared by the method according to any one of claims 1 to 3 in a hydrogenation reaction catalyst.
6. Use of the chemically modified fullerene C60 / Pt catalyst prepared by the method according to any one of claims 1 to 3 as a SPE cathode catalyst in electrochemical hydrogenation of soybean oil.
7. Use of the chemically modified fullerene C60 / Pt catalyst according to claim 6 as a SPE cathode catalyst in electrochemical hydrogenation of soybean oil, characterized in that The reaction conditions of the electrochemical hydrogenation of soybean oil are as follows: reaction temperature 30-80 °C, oil phase flow rate 20-90 mL / min, water phase flow rate 20-90 mL / min, cathode catalyst loading 0.1-0.8 mg / cm 2 The anode catalyst is RuO2, and the anode catalyst loading is 0.1~0.8 mg / cm 2 .
8. The use of the chemically modified fullerene C60 / Pt catalyst according to claim 7 as a SPE cathode catalyst in electrochemical hydrogenation of soybean oil, characterized in that The reaction conditions of the electrochemical hydrogenation of soybean oil are as follows: reaction temperature 50 °C, oil phase flow rate 50 mL / min, water phase flow rate 35 mL / min, cathode catalyst loading 0.4 mg / cm 2 The anode catalyst is RuO2, and the anode catalyst loading is 0.6 mg / cm 2 .
Citation Information
Patent Citations
Preparation method and device for fuel cell membrane electrodes
CN110265671A